A comparative study of Hankel transform filters for marine controlled-source electromagnetic surveys. Issue 6 (1st November 2016) - Jang, Hangilro; Kim, Hee Joon
Abstract: Using a closed-form solution of the Hankel transform in transverse magnetic mode for a homogeneous half-space model, we can assess the accuracy of digital linear filters for evaluating the Hankel transform. In this paper, we conduct comparative performance tests on the linear filter with known integral transforms. We examine three kinds of filters developed by W. L. Anderson, F. N. Kong and H. Mizunaga, which are known to be suitable for marine controlled-source electromagnetic (CSEM) applications. Kong's filters perform best in the three kinds of filters over a practical range of offset distances in marine CSEM surveys. While the relative error versus distance appears as a V-shaped curve in semi-log scale, Mizunaga's filters are the shortest in length and have a performance comparable to Kong's filters. Anderson's filters have a quite similar performance between the J 0 and J 1 filters, although these are somewhat inferior to Kong's and Mizunaga's filters when computing marine CSEM fields.